ANALISIS IMPLEMENTASI KEBIJAKAN RETRIBUSI PARKIR DALAM MENINGKATKAN PENDAPATAN ASLI DAERAH DI KOTA BENGKULU - Purniati, Purniati; Aprianty, Henny; Dani, Rahiman (Mimbar : Jurnal Penelitian Sosial Dan Politik, 2021)
Law Number 23 of 2014 concerning Regional Government mandates that the implementation of regional autonomy adheres to the principle of autonomy as wide as possible, real and responsible. The principle of autonomy as broadly as possible implies that autonomous regions are given the authority to regulate and manage all government affairs, including exploring sources of regional income so that the region becomes advanced and can implement the principle of regional autonomy without depending on other regions. Bengkulu City has an original source of regional revenue, one of which is parking fees. From various case studies in Indonesia, including Bengkulu City, where parking fees are one source of regional income. Zone 6 Panorama Market Bengkulu City is the research location on the grounds that this zone makes a large contribution compared to other zones. This study aims to determine and analyze the implementation of parking retribution policies in increasing Regional Original Income (PAD) in Bengkulu City. The research method used is qualitative evaluation with data collection techniques with direct observation, interviews, documentation. From the results of research conducted that parking fees increase the source of local revenue